\(A=\frac{1}{2}+\frac{2}{2^2}+\frac{3}{2^3}+...+\frac{2018}{2^{2018}}\)
\(\Rightarrow2A=1+\frac{2}{2}+\frac{3}{2^2}+...+\frac{2018}{2^{2017}}\)
\(\Rightarrow2A-A=1+\frac{2}{2}+\frac{3}{2^2}+...+\frac{2018}{2^{2017}}-\frac{1}{2}-\frac{2}{2^2}-\frac{3}{2^3}-...-\frac{2018}{2^{2018}}\)
\(\Rightarrow A=1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{2017}}-\frac{2018}{2^{2018}}\)
Đặt \(B=1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{2017}}\)
\(\Rightarrow2B=2+1+\frac{1}{2}+...+\frac{1}{2^{2016}}\)
\(\Rightarrow2B-B=2+1+\frac{1}{2}+...+\frac{1}{2^{2016}}-1-\frac{1}{2}-...-\frac{1}{2^{2017}}\)
\(\Rightarrow2B-B=2-\frac{1}{2^{2017}}\)
\(\Rightarrow A=2-\frac{2}{2^{2017}}-\frac{2018}{2^{2018}}\)
\(2A=1+\frac{2}{2}+\frac{3}{2^2}+...+\frac{2018}{2^{2017}}\)
\(\Rightarrow2A-A=\left(1+...+\frac{2018}{2^{2017}}\right)-\left(\frac{1}{2}+...+\frac{2018}{2^{2018}}\right)\)
\(\Rightarrow A=1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{2017}}-\frac{2018}{2^{2018}}\)
Đặt \(B=\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{2017}}\)
Tính 2B rùi trừ B ( tương tự nhé )
\(\Rightarrow B=1-\frac{1}{2^{2017}}\)
\(\Rightarrow A=1+1-\frac{1}{2^{2017}}+\frac{2018}{2^{2018}}\)
\(\Rightarrow A=2-\frac{1}{2^{2017}}+\frac{2018}{2^{2018}}\)
\(\Rightarrow A=\frac{2^{2019}-2+2018}{2^{2018}}\)